The homeodomain region controls the phenotype of HOX-induced murine leukemia - Breitinger, Constanze; Mäthner, Emanuel; Garcia-Cuellar, Maria-Paz; Slany, Robert (Blood, 2012)
HOX proteins are widely involved in hematopoietic development. These transcription factors combine a conserved DNAbinding homeobox with a divergent N-terminus that mediates interaction with variable cofactors. The resulting combinatorial diversity is thought to be responsible for mammalian HOX specificity. Contrasting this proposed mechanism for normal HOX function, here we demonstrate that, in the context of hematopoietic immortalization and leukemogenesis, individual HOX properties are governed almost exclusively by the homeodomain. Swap experiments between HOXA1 and HOXA9, 2 members of nonrelated paralog groups, revealed that gene expression patterns of HOX transformed cells in vitro are determined by the nature of the homeodomain. Similar results were seen in vivo during HOX-mediated leukemogenesis. An exchange of the homeodomains was sufficient to convert the slow, low-penetrance phenotype of HOXA1- induced leukemia to the aggressive fastacting disease elicited by HOXA9 and vice versa. Mutation and deletion studies identified several subregions within the DNAbinding domain responsible for paralog specificity. Previously defined binding sites for PBX cofactors within the exchangeable, nonhomeobox segment were dispensable for in vitro oncogenic HOX activity but affected in vivo disease development. The transcriptional activator domain shared by HOXA1 and HOXA9 at the very N-terminus proved essential for all transformation. © 2012 by The American Society of Hematology.